STRATEGI KESEPADANAN PESAN PADA LINGUISTICS ACROSS CULTURE DAN TERJEMAHANNYA - Haryanti, Dwi (Universitas Muhammadiyah Surakarta, 2013)
This descriptive qualitative study aims at describing strategies used by the translator in grasping equivalence. The data are sentences containing the equivalence strategies and their translation into Indonesian taken from âLinguistics Across Cultureâ and âLinguistik di Pelbagai Budayaâ. The data is collected using documentation method and the data is then analyzed using comparative method. The findings show that the equivalence strategies used by the translator of âLinguistics Across Cultureâ into âLinguistik di Pelbagai Budayaâ include addition, deletion, adoption, adaptation, category shift, level shift, and intra-system shift.